Transcranial Doppler in the Diagnosis of Cerebral Vasospasm: An Updated Meta-Analysis. Issue 10 (October 2018) - Mastantuono, Jean-Mathieu; Combescure, Christophe; Elia, Nadia; Tramèr, Martin R.; Lysakowski, Christopher
Abstract : Objectives: To evaluate the performance of transcranial Doppler and transcranial color-coded duplex Doppler in patients with cerebral vasospasm due to aneurysm rupture. Angiography was considered as the gold standard comparator. Data Sources: Search in MEDLINE, Embase, and Central from January 2001 to October 2017, without language restriction. Bibliographies of retrieved articles were screened for additional studies. Study Selection: Randomized studies comparing transcranial Doppler or transcranial color-coded duplex Doppler with angiography in adults. Data Extraction: Data were extracted independently by several investigators. Sensitivity and specificity were combined across studies using a bivariate model. Preferred Reporting Items for Systematic Reviews and Meta-Analyses was used for reporting and Quality Assessment of Diagnostic Accuracy Studies-2 for quality assessment. Data Synthesis: We included 18 studies. Fifteen tested transcranial Doppler. For the middle cerebral artery (10 studies, 1, 408 tests), the pooled sensitivity was 66.7% (95% CI, 55.9–75.9) and specificity was 89.5% (80.3–94.7). Three studies (278 tests) tested transcranial color-coded duplex Doppler for the middle cerebral artery. The pooled sensitivity was 81.5% (66.0–90.0), and specificity was 96.6% (93.0–98.0). For an arbitrarily chosen prevalence of vasospasm of 70%, positive and negative predictive values were 93.7% (88.9–96.6) and 53.4% (46.7–60.9) for transcranial Doppler and 98.2% (96.4–99.1) and 69.1% (56.1–80.9) for transcranial color-coded duplex Doppler. Conclusions: Assuming a high prevalence of vasospasm of the middle cerebral artery, both transcranial Doppler and transcranial color-coded duplex Doppler are likely to detect it, but neither is useful to exclude it. There is no convincing evidence that the accuracy of transcranial color-coded duplex Doppler is any better than that of transcranial Doppler. For arteries other than middle cerebral artery, there is a lack of evidence of the usefulness of transcranial Doppler. Abstract : Supplemental Digital Content is available in the text.